Rancang Bangun Aplikasi Sistem Informasi Penjualan "Gadget-Sale" untuk Pengelolaan Produk dan Transaksi Berbasis Web - Rezki, Muhammad; Nurdiani, Siti; Fahmi Julianto, Muhammad; Murni, Sri (Jurnal Sistem Informasi Akuntansi, 2024)
The rapid advancement of information and communication technology (ICT) has transformed transaction methods across sectors, including product sales. ICT supports information systems that help businesses achieve their objectives. The contraption industry, in particular, has adopted digital platforms to meet market demands, with e-commerce rapidly growing in Indonesia. E-commerce is replacing conventional shopping due to its convenience, comfort, and variety. It relies on WWW technology, databases, email, delivery systems, and payment tools. However, many contraption businesses face challenges in reaching customers effectively due to marketing limitations, disorganized product management, and subpar shopping experiences. To address this, an innovative solution is needed: a web-based online sales platform that simplifies transactions and offers a secure, enjoyable shopping experience. The Gadget-Sale platform aims to meet these needs with a user-friendly interface, comprehensive product catalogs, secure payment systems, and responsive customer service. This platform helps businesses manage inventory, monitor sales trends, and design targeted marketing strategies. This research focuses on designing and developing the Gadget-Sale web-based system to enhance product sales and expand market reach